The advent of corporate limited liability in Prussia 1843 - Cordelius Ilgmann (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2011)
Corporate limited liability has a long and contentious history, stretching back to the mid-19th century and beyond. Initially being hailed as one of the decisive legal invention of our age, recently scholars have highlighted the negative effects of curtailing liability. This in turn has inspired research in the historical origins of liability. While the debate on the adoption of limited liability for joint stock companies in Britain and the United States in the 19th century is comparatively well documented, little is known about the contemporary German debate. Thus, this paper aims to shed light on the debate within the Prussian Government which surrounded the Stock Corporation Act of 1843. Drawing on primary sources of the debate within the Prussian administration in the course of the legislative process, it tries to examine whether limited liability was indeed seen as a prerequisite for the existence of joint-stock companies as its supporters claim. I find that in line with British and American experience limited liability was not universally seen as a necessary condition for incorporated joint-stock companies. In fact, the course of the debate suggests that limited liability was finally introduced because the administration wrongly assumed that joint stock companies always comprised a large number of shareholders with little equity each, being obviously unaware of the possibility of joint stock companies being dominated by large shareholders and institutional investors. Moreover, limited liability for shareholders was regarded as being similar to that of passive sleeping partners, a justification that seems problematic in the light of today's virtually all powerful institutional investors.
Keywords: 330